Bridging Exhibitionism and Internet Pornography: Is There A Link? - Lee, Sze Chet; Loo, Jiann Lin; Hatta Sidi; Hazli Zakaria; Rosliza Yahaya (2018)
Exhibitionism is a distressing condition which may have a link with the increasing availability and usage of online sexual activities (OSA). We highlight a 42-year-old man who presented with a constant craving for OSA to achieve his sexual satisfaction which included exposing his genitalia to virtual partners, unsuspected strangers, and colleagues in public areas. His sexual behaviours were further reinforced by an online video chatting with genitalia exposure, which ended commonly with an exchange of masturbatory acts. He denied any problem with his erection and able to achieve orgasm via common sexual acts. There was no past psychiatric history nor family history of mental disorder. He volunteered to seek psychiatric help and subsequently given a psycho education on his illness and how to cope with the distress associated with his sexual acts. He was scheduled for an intensive psychotherapy to instil insight and hope to deal with his sexual difficulties.